2020
DOI: 10.1175/jcli-d-19-0604.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tropical Variability in Driving Decadal Shifts in the Southern Hemisphere Summertime Eddy-Driven Jet

Abstract: The Southern Hemisphere summertime eddy-driven jet and storm tracks have shifted poleward over the recent few decades. In previous studies, explanations have mainly stressed the influence of external forcing in driving this trend. Here we examine the role of internal tropical SST variability in controlling the austral summer jet’s poleward migration, with a focus on interdecadal time scales. The role of external forcing and internal variability are isolated by using a hierarchy of Community Earth System Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 70 publications
2
57
0
Order By: Relevance
“…During this period, the observed AR frequency has been increasing over the Southern Ocean and decreasing at lower latitude regions at around 30°S. Consistent with this trend pattern, AR events have been systematically shifting poleward, at a rate of 0.24°, 0.27°, and 0.72°latitude per decade for the AR centroid, poleward tip, and landfall location, respectively, consistent with the poleward shift of the westerly jet by 0.30°latitude per decade (Swart et al, 2015, Yang et al, 2020. The annual total precipitation induced by ARs has also been increasing over the Southern Ocean due mostly to the increases in AR frequency over the regions.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…During this period, the observed AR frequency has been increasing over the Southern Ocean and decreasing at lower latitude regions at around 30°S. Consistent with this trend pattern, AR events have been systematically shifting poleward, at a rate of 0.24°, 0.27°, and 0.72°latitude per decade for the AR centroid, poleward tip, and landfall location, respectively, consistent with the poleward shift of the westerly jet by 0.30°latitude per decade (Swart et al, 2015, Yang et al, 2020. The annual total precipitation induced by ARs has also been increasing over the Southern Ocean due mostly to the increases in AR frequency over the regions.…”
Section: Discussionsupporting
confidence: 65%
“…The difference of the thermodynamically and dynamically driven trends between GOGA and LENS are shown in Figures 4g and 4h, respectively. Figure 4g indicates that the enhanced positive trends over the Pacific sector are at least partly driven by circulation changes due to the negative IPO‐like trend (Figure 1f), consistent with the IPO going from positive phase in 1979–1998 to negative phase in 1999–2013, contributing to a poleward shift in the westerly jet (Yang et al, 2020). In addition, the negative IPO‐like SST trend drives widespread drying in the moisture field except wetting in the subtropical region (Figure S8) which also results in widespread decline in AR frequency over the entire Southern Ocean.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…(2015) and D. Yang et al. (2020), who found that a substantial component of recent multidecadal westerly wind variability could be accounted for in model experiments forced by observed tropical SST variations, independent of anthropogenic forcing.…”
Section: Historical Eramentioning
confidence: 97%
“…Our study extends earlier studies by Schneider et al (2015) and Swart et al (2015) who showed that there are spatial variations in past trends in near‐surface winds, but did not examine the impact of these trends on the strength and position of the peak winds averaged over each ocean basin. Yang et al (2020) have very recently examined zonal variations in eddy‐driven jet trends, but they only considered summer trends. We show here that the winter‐spring (and annual‐mean) trends differ substantially from the summer trends.…”
Section: Introductionmentioning
confidence: 99%